Sleep habits and physical activity in health science students – a cross-sectional study - Jha , Jay Prakash; Pun , Dilli Bahadur; Thapa , Bobby; Chaudhary , Hiramani Prasad (Europasian Journal of Medical Sciences, 2024)
Background: Adequate sleep and physical activity are important for health, yet college students often face challenges in both. This study aims to determine the sleep habit and physical activity patterns among undergraduate health science students at Jumla, and to examine the relationship between these variables. Data & Methods: A descriptive cross-sectional study was conducted involving 127 health science students (47 males) of Karnali Academy of Health Sciences, Jumla. Data were collected using a self-administered semi-structured questionnaire to assess sleep habits and physical activity. Descriptive statistics, chi-square test and Pearson correlation were used for data analysis. Results: The study found that 15.75% of students had sleep durations of <7 hours, and 20.47% experienced sleep latency of ≥30 minutes. The mean sleep score was 3.15 ± 2.39, and the mean MET value was 895.02 ± 791.36 MET-min/week. Significant gender differences were observed in sleep quality (median sleep score in females 4 (IQR 2-5) vs males 2 (IQR 0-3), p<0.001) and physical activity (median MET value in females 504.75 (IQR 260 – 893) vs males 1236 (IQR 706.5 – 1742), p < 0.001). There were significant associations between total MET values and sleep duration (r = 0.193, p = 0.03) and between sleep latency and sleep score (r = 0.327, p < 0.001). However, no significant associations were found between sleep quality and physical activity. Conclusions: The physical activity and sleep quality was average in the health science students of Karnanali Academy, but was significantly lower in females than males. Interventions to improve both sleep quality and physical activity among health science students, especially to females might be beneficial.